Effects of Angiotensin II Type 1A Receptor on ACE2, Neprilysin and KIM-1 in Two Kidney One Clip (2K1C) Model of Renovascular Hypertension - Alawi, Laale F.; Dhakal, Sanjeev; Emberesh, Sana E.; Sawant, Harshal; Hosawi, Anhar; Thanekar, Unmesha; Grobe, Nadja; Elased, Khalid M. (Frontiers in Pharmacology, 2021)
Activation of the renin angiotensin system plays a pivotal role in the regulation of blood pressure, which is mainly attributed to the formation of angiotensin-II (Ang II). The actions of Ang II are mediated through binding to the Ang-II type 1 receptor (AT1R) which leads to increased blood pressure, fluid retention, and aldosterone secretion. In addition, Ang II is also involved in cell injury, vascular remodeling, and inflammation. The actions of Ang II could be antagonized by its conversion to the vasodilator peptide Ang (1-7), partly generated by the action of angiotensin converting enzyme 2 (ACE2) and/or neprilysin (NEP). Previous studies demonstrated increased urinary ACE2 shedding in the db/db mouse model of diabetic kidney disease. The aim of the study was to investigate whether renal and urinary ACE2 and NEP are altered in the 2K1C Goldblatt hypertensive mice. Since AT1R is highly expressed in the kidney, we also researched the effect of global deletion of AT1R on renal and urinary ACE2, NEP, and kidney injury marker (KIM-1). Hypertension and albuminuria were induced in AT1R knock out (AT1RKO) and WT mice by unilateral constriction of the renal artery of one kidney. The 24-hour mean arterial blood pressure (MAP) was measured using radio-telemetry. Two weeks after 2K1C surgery, MAP and albuminuria were significantly increased in WT mice compared to AT1RKO mice. Results demonstrated a correlation between MAP and albuminuria. Unlike db/db diabetic mice, ACE2 and NEP expression and activities were significantly decreased in the clipped kidney of WT and AT1RKO compared with the contralateral kidney and sham control (p<0.05). There was no detectable urinary ACE2 and NEP expression and activity in 2K1C mice. KIM-1 was significantly increased in the clipped kidney of WT and AT1KO (p<0.05). Deletion of AT1R has no effect on the increased urinary KIM-1 excretion detected in 2K1C mice. In conclusion, renal injury in 2K1C Goldblatt mouse model is associated with loss of renal ACE2 and NEP expression and activity. Urinary KIM-1 could serve as an early indicator of acute kidney injury. Deletion of AT1R attenuates albuminuria and hypertension without affecting renal ACE2, NEP, and KIM-1 expression.